High-Gain transimpedance amplifier (TIA) for night airglow photometer - Patil, P.T.; Mukherjee, G.K.; Sharma, A.K.; Mudholkar, R.R. (My University, 2009)
This paper describes a simple, inexpensive transimpedance amplifier (TIA) suitable to convert the fast current pulses delivered by photomultiplier tube of night airglow photometer into the corresponding voltage. Design criteria for the transimpedance amplifier are carefully selected to include low input bias current, offset voltage and noise. The operation of the transimpedance amplifier and the theoretical analysis of its gain are discussed. Theoretical and simulated results are compared with that of the developed high gain transimpedance amplifier. Correlations between photometer current readings and voltage output from the transimpedance amplifier are high and linear at both high and low airglow intensities. The test results and simulation involving class-leading FET operational amplifier are presented. A comparative analysis between two photomultiplier tube (PMT) amplifier circuits is carried out. One circuit is based on a conventional transimpedance amplifier connection and the other circuit is based on resistive-tee network connection. The results are satisfactory and show that the photometer amplifier performance can be improved by using resistive-tee network technique. These experimental results also underline the need for careful selection of electronic components, circuit layout and shielding if the capabilities of these devices are to be fully exploited.
Keywords: Photometer; Resistive tee-network; Transimpedance amplifier; Night airglow